Education and Audio-Visual Image: Space for Reflections, Conflicts and Convergence - Soares Dias Vermelho, Sônia Cristina; Machado Velho, Ana Paula; da Silva Macuch, Regiane (VISUAL REVIEW. International Visual Culture Review / Revista Internacional de Cultura Visual, 2015)
The article is the result of research with adolescents where we analyze the audiovisual production experience to understand the content of speech in audiovisual narratives. The hypothesis is that it is possible to use the audiovisual production to mix scientific content and social experience for a formation reflexive criticism. We analyzed 32 short films and we can say that the problems presented in the movies bring the dilemmas and conflicts that society brings adolescents. As experience, education can take ownership of the audiovisual production process as "pedagogical strategy", both to give greater meaning to education, and to "give voice" to these young people. We use the Freudian psychoanalytic theory, critical social theory of the Frankfurt School, in particular Walter Benjamin and Theodor Adorno, and the field of communication theories of Jesus Martin-Barbero and German Rey.